2019
DOI: 10.1002/adhm.201901224
|View full text |Cite
|
Sign up to set email alerts
|

Specific Small‐Molecule NIR‐II Fluorescence Imaging of Osteosarcoma and Lung Metastasis

Abstract: Osteosarcoma is an aggressive tumor of mesenchymal origin that is more likely to spread to the lung than others, with a major impact on patients' prognosis. The optimal imaging method that can reliably detect or exclude pulmonary metastases from osteosarcoma is still scarce. Herein, two homologous types of fluorescent probes CH1055‐PEG‐PT and CH1055‐PEG‐Affibody, which show highly promising results for targeting imaging of osteosarcoma and its lung metastasis, respectively, are designed and synthesized. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…5d). The toxicity of H4-PEG-PT was determined in vitro with an MTT assay on 143B and L929 cells at different concentrations (2,4,8,16, and 32 µM) ( Fig. 5f).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5d). The toxicity of H4-PEG-PT was determined in vitro with an MTT assay on 143B and L929 cells at different concentrations (2,4,8,16, and 32 µM) ( Fig. 5f).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro bone-targeted assay. In order to evaluate the binding ability of H4-PEG-PT and H4, various amount of the probes (2,4,8,16,32, and 64 μM, 500 μL) were incubated with HA (10 mg), respectively, for 4 h at room temperature under mild stirring. Then, the mixture was centrifugated at 1200 rpm for 10 min and washed with 8-fold excess of PBS three times.…”
Section: Subcellular Distribution Of Cytochrome C (Cyto C)mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al designed and synthesized the two homologous forms of fluorescent probes CH1055-PEG-PT and CH1055-PEG-Affibody that show extremely promising results for targeting imaging of OSA and its lung organ metastasis, respectively. it’s found that the close to NIR-II imaging quality of CH1055-PEG-PT is way superior thereto of CT for the first in vivo 143B tumor imaging, and this probe-guided surgery for accurate surgery of 143B tumor [ 82 ].…”
Section: Diagnosis Of Human Osteosarcomamentioning
confidence: 99%
“…Although the combination of chemotherapy and surgery improve its prognosis, many patients still experience recurrence or metastasis [2]. Pulmonary metastasis is the most common cause of death for osteosarcoma patients [3]. Therefore, identifying reliable biomarkers for osteosarcoma metastasis and prognosis can provide attractive potential targets and prognostic evaluation.…”
Section: Introductionmentioning
confidence: 99%